2023
DOI: 10.3389/fnsys.2023.919977
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning approaches and non-linear processing of extracted components in frontal region to predict rTMS treatment response in major depressive disorder

Abstract: Predicting the therapeutic result of repetitive transcranial magnetic stimulation (rTMS) treatment could save time and costs as ineffective treatment can be avoided. To this end, we presented a machine-learning-based strategy for classifying patients with major depression disorder (MDD) into responders (R) and nonresponders (NR) to rTMS treatment. Resting state EEG data were recorded using 32 electrodes from 88 MDD patients before treatment. Then, patients underwent 7 weeks of rTMS, and 46 of them responded to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 88 publications
1
3
0
Order By: Relevance
“…Our results indicated that responders to rTMS treatment had significantly less beta power than non-responders in baseline resting EEG recordings in both eyes-open and eyes-closed combined conditions. The result was similar to those reported by Hasanzadeh et al, which they reported high predictive accuracy of 91.3% for beta power 14 , and Ebrahimzadeh et al 24 , who also reported that beta power predicted response to rTMS treatment for depression. However, our result extends their results by demonstrating that the differences in beta power are present in both the resting eyes-closed condition and the eyes open resting state (in contrast to the previous research which only examined the eyes closed state) 14 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results indicated that responders to rTMS treatment had significantly less beta power than non-responders in baseline resting EEG recordings in both eyes-open and eyes-closed combined conditions. The result was similar to those reported by Hasanzadeh et al, which they reported high predictive accuracy of 91.3% for beta power 14 , and Ebrahimzadeh et al 24 , who also reported that beta power predicted response to rTMS treatment for depression. However, our result extends their results by demonstrating that the differences in beta power are present in both the resting eyes-closed condition and the eyes open resting state (in contrast to the previous research which only examined the eyes closed state) 14 .…”
Section: Discussionsupporting
confidence: 90%
“…The correlation dimension has also been used to differentiate people with and without depression with high accuracy compared to other non-linear features (i.e., detrended fluctuation analysis, Higuchi fractal and Lyapunov exponent) 23 . Interestingly, two recent studies using machine learning techniques found that beta power and correlation dimension accurately predicted clinical response to rTMS 14,24 , holding promise for potential clinical application. However, robust determination of an effect that might be used clinically requires replication in independent datasets.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, some signal patterns are lost due to filtering, but the spectral analysis of the signal shows that the removed patterns are not in the frequency range of the alpha and beta bands [56][57][58][59]. In this method, after filtering, the SNR is calculated to check the effect of the filter on the signal.…”
Section: Preprocessingmentioning
confidence: 99%
“…EEG (electroencephalography) is a technique employed to monitor brain activity through the measurement of voltage changes generated by the collective neural activity within the brain ( San-Segundo et al, 2019 ; Dehghani et al, 2020 , 2022 , 2023 ; Sadjadi et al, 2021 ; Mosayebi et al, 2022 ). EEG serves as a reflection of the brain’s activity and functioning, and it finds diverse applications, including but not limited to emotion recognition ( Dehghani et al, 2011a , b , 2013 ; Ebrahimzadeh and Alavi, 2013 ; Nikravan et al, 2016 ; Soroush et al, 2017 , 2018a , b , 2019a , b , 2020 ; Bagherzadeh et al, 2018 ; Alom et al, 2019 ; Ebrahimzadeh et al, 2019a , b , c , 2021 , 2022 , 2023 ; Bagheri and Power, 2020 ; Karimi et al, 2022 ; Rehman et al, 2022 ; Yousefi et al, 2022 , 2023 ).…”
Section: Introductionmentioning
confidence: 99%